2019
DOI: 10.1136/neurintsurg-2019-014966
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of stent apposition after stent-assisted coiling of intracranial aneurysms using high resolution 3D fusion images acquired by C-arm CT

Abstract: PurposeWe used an imaging technique based on 3-dimensional (3D) C-arm CT to assess the apposition of three types of stents after coiling of intracranial aneurysms.MethodsAll patients with intracranial aneurysms were considered who received stent-assisted coiling with Enterprise2, Neuroform EZ, or Neuroform Atlas stents confirmed by C-arm CT imaging at our institution between June 2015 and November 2017. A 3D digital subtraction angiography (DSA) scan for vessel imaging followed by a high-resolution cone beam C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Herweh et al [ 7 ] first studied the application of the EP2 stent in clinical patients and reported good safety and effectiveness; however, incomplete stent apposition still occurred in the vessels with a large curvature. Kato et al [ 14 ] used the double volume fusion technique based on C-arm CT to compare stent-vessel apposition of three stents (EP2, Neuroform, and Atlas) and found the frequency of crescent sign detection in the bending vessels was highest for the EP2 stent (27%, 8%, and 0, respectively). Chen et al [ 15 ] used VasoCT to observe EP2 stent release and reported that 6 of 25 stents (24%) showed malposition: 2 showed kinking and the other 4 showed large gaps between the stent and vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Herweh et al [ 7 ] first studied the application of the EP2 stent in clinical patients and reported good safety and effectiveness; however, incomplete stent apposition still occurred in the vessels with a large curvature. Kato et al [ 14 ] used the double volume fusion technique based on C-arm CT to compare stent-vessel apposition of three stents (EP2, Neuroform, and Atlas) and found the frequency of crescent sign detection in the bending vessels was highest for the EP2 stent (27%, 8%, and 0, respectively). Chen et al [ 15 ] used VasoCT to observe EP2 stent release and reported that 6 of 25 stents (24%) showed malposition: 2 showed kinking and the other 4 showed large gaps between the stent and vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Atlas has less metal volume than Enterprise and protrudes into the unconstrained segment. 8 Therefore, it is unlikely that LVIS expansion is affected within the Atlas. Since LVIS expansion was not restricted by the Atlas, the transition zone was shortened, which may have led to aneurysm occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…HR-FDCT has helped improve stent visualization during neurointerventional procedures (Clarençon et al, 2017;Kuriyama et al, 2018;Srinivasan et al, 2018). Studies have explored its utility in patients with intracranial aneurysms [ (Caroff et al, 2014;Shintai et al, 2018;Kato et al, 2020). However, few reports have focused on the clinical application of HR-FDCT in stent placement for symptomatic ICAS.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients who develop recurrent cerebral infarction or recurrent transient ischemic attacks (TIAs) despite optimal medical therapy may be considered for more aggressive treatment, including cerebral arterial angioplasty and/or stent placement (Qureshi and Caplan, 2014;Heit and Wintermark, 2018). Optimal visibility of the intracranial stent is limited using digital subtraction angiography (DSA) applications (Kato et al, 2020). Although some radiopaque elements of intracranial stents may be observed via fluoroscopy during treatment, local distortion or incomplete expansion of the stent may be difficult to identify due to limited angiographic angles or the presence of bony or metal obstructions (Li et al, 2019).…”
Section: Introductionmentioning
confidence: 99%